Fundos mobiliários e meios alternativos de garantia do juízo por investidores institucionais: discurso sobre eficiência e custo de oportunidade - Costa, Josué Hoff da (Universidade do Vale do Rio dos Sinos, 2017)
It was intended to elucidate whether the execution court's guarantee, promoted by alternative means such as securities funds, in the specific case of a qualified investor, to the detriment of the means preferably admitted by the Judiciary, not shared or pecuniary deposit in account linked to the process, Pareto-efficient and inconsiderate the existence of opportunity cost. The object sought was analyzed, based on a case study, analyzing a receptivity of the judiciary about of the security investment fund intended to guarantee execution court, considering a sample of the judicial processes involved. All decisions rendered by the Superior Court of Justice and the Court of Justice of Rio Grande do Sul were considered too, taking into account the admissibility of the furniture fund for the chosen scope (jurimetrics). It was found that the asset adopted as a paradigm was admitted in most of the cases confronted, especially when it is not a creditor insurgency, unlike what occurred when the subject was tried in the second degree of jurisdiction. The security fund used by institutional investors for the guarantee of the execution court proved Pareto-efficient in relation to the pecuniary deposit, for both the Debtor and the Creditor, considering the safety and liquidity of the asset. In spite of this, in cases where the Judiciary was effectively provoked (when there was an objection from the creditor), it preferred the adoption of the traditional pecuniary means, despite the opportunity cost involved, which has been shown to be caused by path dependence, rather than agent problem, not categorically evidenced. In cases where the judiciary was confronting, there was no pronouncement on allocative efficiency. Both the precedent coming from Topic number 913 of the STJ and the systematicity of the legal order of the country admit the adoption of the most efficient alternative means, especially in the case of institutional investors.
Keywords: Eficiência; Fundo mobiliário; Garantia do juízo; Custo de agência; Custo de oportunidade; Dependência da trajetória; Efficiency; Security investment fund; Court guarantee; Agency costs; Opportunity cost; Path dependence; ACCNPQ::Ciências Sociais Aplicadas::Direito